Investigation of Model of Helix with Exteriore Shields - Skudutis, J.; Daskevicius, V. (Elektronika ir Elektrotechnika, 2000)
In the present study the model of the flat helical retard system was investigated. Formulas for the moderation coefficient and characteristic impedance were made more exact. It was shown that the model well reflected the processes in the helical retard system and it could be applied for the investigation of the flat homogeneus and nonhomogeneus helical systems.